Patterns and Determinants of International Activities: Are SMEs Different? - Heinz Hollenstein (Austrian Institute of Economic Research (WIFO), 2001)
The literature on the internationalisation of firms has paid little attention to SMEs. SME-oriented studies are predominantly descriptive or illustrating theoretical arguments, and those dealing with services are mostly confined to specific industries. The paper aims at correcting some of these deficiencies. To this end, we start with characterising the international activities of Swiss-based firms with special emphasis on differences by size and sector. The pattern we find for SMEs is broadly in line with theory and (the somewhat fragmentary) empirical evidence. The main part of our contribution is devoted to identifying econometrically, based on firm-level data, the factors determining international activities of SMEs. The analysis confirms Dunning's "Ownerhip-Location-Internalisation" paradigm, with ownership-specific advantages being the main drivers, irrespective of firm size, sector and internationalisation strategy (in terms of business functions transferred abroad). However, we also find important differences by firm size: Location-specific advantages foster international activities only in case of SMEs; internalising advantages are relevant primarily for large firms; application-oriented knowledge and foreign experience are particularly relevant ownership-specific advantages in case of SMEs, whereas R&D is an ownership advantage of prime importance for large firms. Both the descriptive and the explicative analysis imply that international and domestic activities are complements.
Keywords: F20; F21; F23; 330; Globalisation; Foreign direct investments (FDI); Internationalisation of business functions; Small and medium-sized firms (SMEs); OLI paradigm; KMU; Internationale Geschäftsbeziehungen; Auslandsinvestition; Schätzung; Schweiz